MEDICINAL USAGE OF AGARWOOD RESIN IN FORM OF ESSENTIAL OIL: A REVIEW - Wangiyana, I Gde Adi Suryawan (Jurnal Silva Samalas, 2019)
Agarwood is a high value of non-timber commodities from Indonesia. Agarwood trade on Indonesia mostly being sold in form of raw material. This raw material is agarwood resin or also well known as â€gubalâ€™. Processing gubal into essential oil will improve the quality and price of this commodity. Furthermore, agarwood essential oil has been reported being used as traditional medication in some countries. This medicinal activity of agarwood essential oil has been confirmed by clinical research and resulted that this material has antioxidant, antibacterial, antifungal and anticancer activity. This material also has neural activity on the nervous system and becomes a potential antidepressant, relaxative, sedative and analgesic agent. The promising of the medicinal use of agarwood essential oil suggested that processing agarwood resin into essential oil should be the number one priority on agarwood trade.